2007
DOI: 10.1007/s10593-007-0157-z
|View full text |Cite
|
Sign up to set email alerts
|

4-hydroxy-2-quinolones 125. Ethyl 3-bromo-2,4-dioxo-1,2,3,4-tetrahydroquinoline-3-carboxylates as potential brominating agents

Abstract: The spatial structural features of 3-bromo-3-ethoxycarbonyl-2,4-dioxo-1,2,3,4-tetrahydroquinolines have been studied by X-ray analysis. It has been experimentally confirmed that these compounds can be regarded as potential brominating agents.The bromination route of ethyl 1R-4-hydroxy-2-oxo-1,2-dihydroquinoline-3-carboxylic acids using molecular bromine in acetic acid depends on the presence of water in the reaction mixture. Its presence predetermines the formation of 1-R-3-bromo-3-ethoxycarbonyl-2,4-dioxo-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Ukrainets and co-workers found that 3-bromo-3-(ethoxycarbonyl)-2,4-dioxo-1,2,3,4-tetrahydroquinones could be regarded as potential brominating agents. 1128 They studied the reaction product of this reagent with cyclohexene in anhydrous carbon tetrachloride in the presence of a catalytic amount of peroxide. The product is a mixture, the main components of which are 3bromocyclohexene (11%) and trans-1,2-dibromocyclohexane (78%) (Scheme 383).…”
Section: Arrieta Et Al Used 4-(dimethylamino)pyridinium Bromidementioning
confidence: 99%
“…Ukrainets and co-workers found that 3-bromo-3-(ethoxycarbonyl)-2,4-dioxo-1,2,3,4-tetrahydroquinones could be regarded as potential brominating agents. 1128 They studied the reaction product of this reagent with cyclohexene in anhydrous carbon tetrachloride in the presence of a catalytic amount of peroxide. The product is a mixture, the main components of which are 3bromocyclohexene (11%) and trans-1,2-dibromocyclohexane (78%) (Scheme 383).…”
Section: Arrieta Et Al Used 4-(dimethylamino)pyridinium Bromidementioning
confidence: 99%
“…For general background, see: Ukrainets et al (2004Ukrainets et al ( , 2007. For chemical bond lengths, see: Bü rgi & Dunitz (1994).…”
Section: Related Literaturementioning
confidence: 99%